Implications of the Job Creation Law for Regional Authority in Environmental Protection and Management - Muhammad Fikri; Muhammad Akbar Azhari; M. Bembo Jati Perdana (The Future of Education Journal, 2026)
Following the enactment of Law Number 11 of 2020 concerning Job Creation, fundamental changes have occurred in the environmental protection and management regime in Indonesia, particularly regarding the provisions regulated under Law Number 32 of 2009 concerning Environmental Protection and Management. These changes include the elimination, amendment, and introduction of new legal norms that significantly affect the environmentally based business licensing system. One of the most prominent implications is the shift of authority from local governments to the central government, particularly in terms of policy formulation, the issuance of environmental permits, and supervision of business activities with potential environmental impacts. Under the previous regulatory regime, local governments played a strategic role in the environmental licensing process, including the assessment of Environmental Impact Assessment (EIA/AMDAL) documents and the issuance of environmental permits. However, following regulatory reform through the Job Creation Law, the environmental licensing system has been integrated into a risk-based business licensing scheme, which places the central government as the dominant authority in decision-making processes. This shift has resulted in reduced local government autonomy in managing and protecting the environment within their respective regions, while also creating the potential for disharmony between central policies and local needs. This study employs a legal material analysis method with a qualitative approach based on library research. Data collection was conducted through an examination of relevant laws and regulations, legal doctrines, and scientific literature, which were further supported by expert opinions in the fields of environmental law and administrative law. This approach aims to obtain a comprehensive understanding of changes in legal norms and their implications for the authority of local governments. The purpose of this study is to examine and analyze in depth the authority of local governments in environmental protection and management after the enactment of the Job Creation Law, particularly concerning changes in the substance of environmental licensing regulations. Furthermore, this study also aims to identify the centralization of authority by the central government, which was previously under the domain of local governments, as well as its implications for the principle of regional autonomy and the effectiveness of environmental protection in Indonesia.